2022
DOI: 10.1002/uog.24957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic criteria for significant anal sphincter defects between endoanal and transperineal ultrasound

Abstract: What are the novel findings of this work?Transperineal ultrasound (TPUS) had excellent agreement with endoanal ultrasound in diagnosing the presence of anal sphincter defects. However, there was poor-to-moderate agreement between the two modalities in the measurement of defect angle, with a standard error of measurement of 16 • and 27 • for external and internal anal sphincter defects, respectively. What are the clinical implications of this work?A cut-off angle of 30 • should not be used for the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Moreover, we found that, in comparison to TPUS, EAUS has the strongest association with anal incontinence symptoms up to 2 years following OASI 7 . The take‐home message of our study 1 is that the defect angle measurement obtained on EAUS is not equivalent to that of TPUS for the same reason acknowledged by Dietz and Shek, namely, that EAUS distends the anal canal.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Moreover, we found that, in comparison to TPUS, EAUS has the strongest association with anal incontinence symptoms up to 2 years following OASI 7 . The take‐home message of our study 1 is that the defect angle measurement obtained on EAUS is not equivalent to that of TPUS for the same reason acknowledged by Dietz and Shek, namely, that EAUS distends the anal canal.…”
mentioning
confidence: 51%
“…We appreciate Prof. Dietz and Dr Shek's interest in our publication 1 . We agree that transperineal ultrasound (TPUS) is less intrusive than endoanal ultrasound (EAUS), but in our practice we perform both examinations, as can be seen in a number of our publications.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…We used a well‐validated imaging modality 7 , 9 to assess any sphincter defects and a validated symptom scoring system 12 . While endoanal ultrasound is a recommended form of imaging, the appearance of a ‘normal’ IAS has not been examined as thoroughly as that of a ‘normal’ EAS.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in multiple imaging modalities, such as translabial or introital ultrasound, for the diagnosis of obstetric anal sphincter injury (OASI), especially for use in a ‘rule‐out’ capacity 6 . Endoanal 7 and translabial 8 ultrasound have been found to be in good agreement for the diagnosis of sphincter trauma 9,10 , though validation of both for the IAS is limited 11 . Despite these advances in imaging technology, the diagnosis of OASI immediately following delivery is based on clinical suspicion and the accoucheur's clinical acumen.…”
Section: Introductionmentioning
confidence: 99%